Antioxidant enzymes in women with endometrial polyps: relation with sex hormones - Pejić, Snežana A.; Kasapović, Jelena D.; Todorović, Ana U.; Stojiljković, Vesna R.; Gavrilović, Ljubica V.; Popović, Nataša M.; Pajović, Snežana B. (European journal of obstetrics & gynecology and reproductive biology, 2013)
To investigate whether antioxidant enzyme activities (superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase) and lipid hydroperoxide levels in patients with endometrial polyps are influenced by the changes in sex hormones (estradiol, progesterone, FSH, and LH) during the menstrual cycle and in postmenopause. The material consisted of blood and endometrial tissue specimens from women diagnosed with endometrial polyps. Patients were divided into groups depending on the phase of the menstrual cycle – follicular or luteal – and the postmenopause. The activities of antioxidant enzymes and the lipid hydroperoxide levels were compared among the phases and a linear regression model was used to evaluate the associations between hormones and antioxidant/oxidant variables. In the blood of examined women, a significant difference in superoxide dismutase activity and lipid hydroperoxide levels was recorded among the phases. There was also a positive correlation between the estradiol concentration and superoxide dismutase. In polyp tissue, we recorded a phase-related difference in superoxide dismutase and glutathione peroxidase activities as well as in the lipid hydroperoxide levels. A negative correlation was observed between FSH/LH and glutathione peroxidase, and between LH and superoxide dismutase. Antioxidant enzymes and lipid hydroperoxide levels in patients with endometrial polyps are influenced by the changes in sex hormones during the menstrual cycle and after the menopause, pointing to a role of the observed relationship in polyp etiology.